Respuesta :
[tex]8-4(a-1)=2+3(4-a) \\
8-4a+4=2+12-3a\\
-3a+4a=12-2-12\\
a=-2[/tex]
Answer:
-2
Step-by-step explanation:
Simplifying
8 + -4(a + -1) = 2 + 3(4 + -1a)
Reorder the terms:
8 + -4(-1 + a) = 2 + 3(4 + -1a)
8 + (-1 * -4 + a * -4) = 2 + 3(4 + -1a)
8 + (4 + -4a) = 2 + 3(4 + -1a)
Combine like terms: 8 + 4 = 12
12 + -4a = 2 + 3(4 + -1a)
12 + -4a = 2 + (4 * 3 + -1a * 3)
12 + -4a = 2 + (12 + -3a)
Combine like terms: 2 + 12 = 14
12 + -4a = 14 + -3a
Solving
12 + -4a = 14 + -3a
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Add '3a' to each side of the equation.
12 + -4a + 3a = 14 + -3a + 3a
Combine like terms: -4a + 3a = -1a
12 + -1a = 14 + -3a + 3a
Combine like terms: -3a + 3a = 0
12 + -1a = 14 + 0
12 + -1a = 14
Add '-12' to each side of the equation.
12 + -12 + -1a = 14 + -12
Combine like terms: 12 + -12 = 0
0 + -1a = 14 + -12
-1a = 14 + -12
Combine like terms: 14 + -12 = 2
-1a = 2
Divide each side by '-1'.
a = -2
Simplifying
a = -2